Modeling and Simulation of LSPMSM for Estimation of Thermal Effect during Different Load Condition - Bala, Mousumi Jana; Jana, Chandan; Chowdhury, Suparna Kar; Sil, Arindam Kumar (International Journal of Computer Sciences and Engineering, 2023)
In this work a methodology to estimate the effect of elevated temperature on a Line Start Permanent Magnet Synchronous Motor (LSPMSM) has been proposed. A simulated model of LSPMSM has been developed for Finite Element Analysis (FEA). The losses obtained from FEA were fed to a Lumped Parameter Thermal Network (LPTN) developed for LSPMSM in the LTSpice environment. The extent of demagnetisation was estimated and the FEA was conducted to identify the change in motor performance. The thermal modeling of the motor has been developed to evaluate the increase in temperature at different parts of LSPMSM under three different load conditions and even after switching off the motor. The results so obtained were validated on a physical setup. The results were analysed to ascertain the performance of the permanent magnets in LSPMSM.